Survey about the potential effects of economic downturn on alcohol consumption, smoking and quality of life in a sample of Central Italy population - Petrelli, Fabio; Grappasonni, Iolanda; Peroni, Annalisa; Kracmarova, Lenka; Scuri, Stefania (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Negative health effects have been associated with the changes in lifestyles in relation with the low income of population. Consequently, in our study we investigated the frequency changes of alcohol and smoke consumption, physical activity, and quality of life in families of Marche Region in Central Italy. Methods: In the period 2016-2017, an anonymous questionnaire has been distributed to junior highschool students of Camerino, Fabriano, and Civitanova Marche of Marche Region. The Manchester Short Assessment of Quality of Life (MANSA), was used to assess subjective quality of life. Results: Data obtained in this research were used to analyze lifestyle changes, specifically those involving alcohol consumption, smoking, and physical activity, and to assess perceived general quality of life. In all categories of population, an increase of frequency in alcohol consumption was observed. On the contrary, for the tobacco smoke we observed a reduction in particular in the parents category. The MANSA mean value was 4.5 with a Standard Deviation of 1.3. Conclusions: As underlighted, also, by results of the MANSA test we can hypothesize a reduction in the family income produces a change of lifestyles.